A Novel Mechanism of Immune Memory Unveiled at the Invertebrate–Parasite Interface. Issue 5 (May 2016) - Coustau, Christine; Kurtz, Joachim; Moret, Yannick
Abstract : Pinaud et al. recently provided the first global investigation of the molecular processes underlying innate immune memory in an invertebrate species. They showed that the memory response of the snail Biomphalaria glabrata to Schistosoma mansoni infection is associated with a shift from cellular to humoral mechanisms.